Extraction and Determination of Nitrite using Ethanol-(NH4)2SO4 Aqueous Two-Phase System - Liu, Ying-Hong; Cai, Qiao; Ma, Wei-Xing (Asian Journal of Chemistry, 2011)
The extraction and determination of nitrite using ethanol-(NH4)2SO4 aqueous two-phase system was investigated. The diazotized product between nitrite and amino black 10B was found to be extracted to the ethanol phase with little interference. The absorbance variation, which was proportional to the concentration of nitrite, was determined at the wavelength of 520 and 620 nm. Beer's law was obeyed over the concentration range of 0-3.3 μg mL-1. By superposing the absorbance at the two wavelength, the apparent molar absorption coefficient was 1.4 × 104 L mol-1 cm-1. The proposed extraction method had been applied to the determination of nitrite in food samples. The results obtained by this method was in good agreement with the results obtained by naphthyl ethylenediamine spectrophotometry method.